Desain 3D Rak Gudang untuk Modul IZI Analytics dengan Three.Js Menggunakan Metode Agile - Pratama, Reza Fauzan; Suhendi, Suhendi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The design of this 3D warehouse-shelf visualization feature aims to address PT Derma Konsep Estetika’s challenges in visually managing stock items through the IZI Analytics module developed by IZIAPP. The Three.js-based visualization enables users to easily identify expired items, empty stock, and stock movement status within a three-dimensional warehouse layout. Key features include camera rotation, hover and click interactions to display product details, and color-coded shelf blocks based on stock status (fast-moving, medium-moving, and slow-moving). The system was developed iteratively using the Agile methodology. Testing through User Acceptance Testing (UAT) showed a 100% user satisfaction rating for the developed features. These results indicate that 3D visualization can serve as an effective initial solution for managing the company's stock inventory.